Predictors of prolonged length of stay in adult patients with respiratory syncytial virus infections – a multi-center historical cohort study - Malik, Ambreen; Szpunar, Susan; Sharma, Mamta; Johnson, Leonard B.; Saravolatz, Louis; Bhargava, Ashish (Frontiers in Microbiology, 2024)
Several studies have reported risk factors for severe disease and mortality in hospitalized adults with RSV infections. There is limited information available regarding the factors that affect the duration of a patient's hospital length of stay (LOS).This was a multicenter historical cohort study of adult patients hospitalized for laboratoryconfirmed RSV in Southeast Michigan between January 2017 and December 2021. Hospitalized patients were identified using codes from the International Classification of Diseases, Tenth Revision codes for RSV infection. Mean LOS was computed; prolonged LOS was defined as greater than the mean.We included 360 patients with a mean age (SD) of 69.9±14.7 years, 63.6% (229) were female and 63.3% ( 228) of white race. The mean hospital LOS was 7.1 + 5.4 days. Factors associated with prolonged LOS in univariable analysis were older age, BMI, smoking status, Charlson Weighted Index of Comorbidity (CWIC), home oxygen, abnormal chest x-ray (CXR), presence of sepsis, use of oxygen, and antibiotics at the time of presentation. Predictors for prolonged LOS on admission in multivariable analysis were age on admission (p<0.001), smoking status (p=0.001), CWIC (p=0.038) and abnormal CXR (p=0.043).Our study found that age on admission, smoking history, higher CWIC, and abnormal CXR on admission were significantly associated with prolonged LOS among adult patients hospitalized with RSV infection. These findings highlight the significance of promptly recognizing and implementing early interventions to mitigate the duration of hospitalization for adult patients suffering from RSV infection.